An efficient and practical entry to 2-amido-dienes and 3-amido-trienes from allenamides through stereoselective 1,3-hydrogen shifts - Hayashi, Ryuji; Feltenberger, John B.; Lohse, Andrew G.; Walton, Mary C.; Hsung, Richard P. (Beilstein Journal of Organic Chemistry, 2011)
Preparations of de novo acyclic 2-amido-dienes and 3-amido-trienes through 1,3-hydrogen shifts from allenamides are described. These 1,3-hydrogen shifts could be achieved thermally or they could be promoted by the use of Brønsted acids. Under either condition, these processes are highly regioselective in favour of the α-position, and highly stereoselective in favour of the E-configuration. In addition, 6π-electron electrocyclic ring-closure could be carried out with 3-amido-trienes to afford cyclic 2-amido-dienes, and such electrocyclic ring-closure could be rendered in tandem with the 1,3-hydrogen shift.
Keywords: allenamides; 2-amido-dienes; 3-amido-trienes; electrocyclic ring-closure; 1,3-hydrogen shift; isomerization